Comparative anatomical study of underground and aboveground organs in Ferula tadshikorum Pimenov under natural and introduced environments - Khamraeva, Dilovar T.; Tukhtaeva, Dinara N.; Khojimatov, Olim K.; Bussmann, Rainer W. (Acta Biologica Sibirica, 2024)
A comparative study was conducted on the anatomical structure of the roots and leaves of Ferula tadshikorum, a rare plant species. The study included two groups: virginile plants introduced at the age of 4 years (located in the Tashkent Botanical Garden) and natural individuals aged 12-14 years (found in the Surkhandarya region, Babatag ridge). The main objective was to understand how the plant’s anatomy changes with age and its adaptation to different environments. Common characteristics were identified in the leaves of both groups of plants. These included the isolateral palisade type of mesophyll, a rounded triangular shape around the central vein, and the presence of 2-layer elongated palisade tissue on the flattened lateral parts from the adaxial side. Regarding the root structure, significant differences were observed between the natural and introduced plants. In the natural samples, the woody part of the root exhibited groups of libriform cells, which seemed to be influenced by the edaphotype (soil conditions) and age of the plant. These findings suggest that the conductive system of the roots develops differently depending on the age and environment. The introduction of Ferula tadshikorum in the Tashkent Botanical Garden proved to be successful, as evident from the results. The leaves of the introduced plants showed adaptive characteristics, such as a thickened outer wall of the epidermis, collenchyma strands, bast fibers, and the isolateral palisade type of mesophyll. These adaptations are likely to help the plant cope with its new environment. In the roots of both natural and introduced plants, an important adaptive function was observed. The parenchymal cells were filled with starch grains, and there was an abundance of secretory ducts. This suggests that the root acts as an accumulating organ for organic substances, aiding the plant’s survival and growth. In conclusion, the study provided valuable insights into the anatomical changes of Ferula tadshikorum at different stages of its life and in different environments. The observed adaptations in the leaves and roots contribute to the plant’s ability to thrive in varying conditions.